Analisis Kajian Semantik Pada Cerpen Ihwal Nama Majid Pucuk Sebagai Bahan Ajar Kelas XI SMAN 1 Telukjambe Timur Kabupaten Karawang - Nisrina Shani Aziza; Dewi Suprihatin; Slamet Triyadi (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study aims to describe the types of meaning contained in the short story collection Ihwal Nama Majid Pucuk through a semantic study and to produce a recommendation for handout teaching material in learning short story texts for grade XI of senior high school. This research employs a qualitative approach with a descriptive method and a text-analysis model, while the data consist of word, phrase, and sentence quotations collected through documentation techniques. The main theory used is Abdul Chaer's theory of meaning, supported by Geoffrey Leech's theory of associative meaning, with data analysis following the stages of data reduction, data display, and conclusion drawing. The results show that the three analyzed short stories contain eight types of meaning, namely lexical and grammatical meaning, referential and nonreferential meaning, denotative and connotative meaning, word and term meaning, conceptual and associative meaning, idiomatic meaning, figurative meaning, as well as locutionary, illocutionary, and perlocutionary meaning. Lexical and grammatical meanings dominate the findings, while proverbial meaning is not found in the data source. The diversity of these meanings confirms that this short story collection is suitable to be used as handout teaching material for short story texts in grade XI of senior high school. Abstrak. Penelitian ini bertujuan mendeskripsikan jenis-jenis makna yang terkandung dalam kumpulan cerita pendek Ihwal Nama Majid Pucuk melalui kajian semantik sekaligus menghasilkan rekomendasi bahan ajar handout pada pembelajaran teks cerpen kelas XI SMA. Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif dan model analisis teks, sedangkan data berupa kutipan kata, frasa, dan kalimat yang dikumpulkan melalui teknik dokumentasi. Teori utama yang digunakan adalah teori makna Abdul Chaer dan teori pendukung makna asosiatif Geoffrey Leech, dengan analisis data mengikuti tahapan reduksi data, penyajian data, serta penarikan simpulan. Hasil penelitian menunjukkan bahwa dalam ketiga cerpen yang dianalisis ditemukan delapan jenis makna, yaitu makna leksikal dan gramatikal, makna referensial dan nonreferensial, makna denotatif dan konotatif, makna kata dan istilah, makna konseptual dan asosiatif, makna idiomatikal, makna kias, serta makna lokusi, ilokusi, dan perlokusi. Makna leksikal dan gramatikal mendominasi temuan, sementara makna peribahasa tidak ditemukan dalam sumber data. Keberagaman makna tersebut menegaskan bahwa kumpulan cerpen ini layak dijadikan bahan ajar handout teks cerpen kelas XI SMA.